Pengembangan Game Animasi untuk Meningkatkan Aspek Nilai Agama Moral TK Muslimat NU 01 Gresik - Ika Ainun Munzilin (Universitas Muhammadiyah Gresik, 2022)
Abstrack This study aims to determine the results of the development of animated multimedia games in distinguishing good behavior and bad behavior using a computer application, namely Power Point. This type of research is development (research and development). Data collection techniques using observation, interviews, documentation, and questionnaires. The results showed that the assessment of the material expert got an average score of 21 which had a percentage of 75% with the criteria of